Effects of Noninvasive Low-Intensity Focus Ultrasound Neuromodulation on Spinal Cord Neurocircuits In Vivo. (27th November 2021) - Liao, Ye-Hui; Chen, Mo-Xian; Chen, Shao-Chun; Luo, Kai-Xuan; Wang, Bin; Liu, Yao; Ao, Li-Juan
Abstract : Although neurocircuits can be activated by focused ultrasound stimulation, it is unclear whether this is also true for spinal cord neurocircuits. In this study, we used low-intensity focused ultrasound (LIFU) to stimulate lumbar 4–lumbar 5 (L4–L5) segments of the spinal cord of normal Sprague Dawley rats with a clapper. The activation of the spinal cord neurocircuits enhanced soleus muscle contraction as measured by electromyography (EMG). Neuronal activation and injury were assessed by EMG, western blotting (WB), immunofluorescence, hematoxylin and eosin (H&E) staining, Nissl staining, enzyme-linked immunosorbent assay (ELISA), immunohistochemistry (IHC), somatosensory evoked potentials (SEPs), motor evoked potentials (MEPs), and the Basso–Beattie–Bresnahan locomotor rating scale. When the LIFU intensity was more than 0.5 MPa, LIFU stimulation induced soleus muscle contraction and increased the EMG amplitudes (P < 0.05 ) and the number of c-fos- and GAD65-positive cells (P < 0.05 ). When the LIFU intensity was 3.0 MPa, the LIFU stimulation led to spinal cord damage and decreased SEP amplitudes for electrophysiological assessment (P < 0.05 ); this resulted in coagulation necrosis, structural destruction, neuronal loss in the dorsal horn by H&E and Nissl staining, and increased expression of GFAP, IL-1 β, TNF- α, and caspase-3 by IHC, ELISA, and WB (P < 0.05 ). These results show that LIFU can activate spinal cord neurocircuits and that LIFU stimulation with an irradiation intensity ≤1.5 MPa is a safe neurostimulation method for the spinal cord.